Clothing management application - Lai, Ting Ting (Universiti Malaysia Sarawak (UNIMAS), 2013)
Based on the reviews of five existing clothing management applications in the market, not all of the clothing management application can cater for users' needs: there is no processing technique for matching the clothes do not have the option to enter their clothes preferences, do not have the function to compare between two selected clothes and do not have user guide or suggestions/tips when user encounters with any problems. Hence, MyCloths (clothing management application) for Android mobile phone is created in this project V-Model is used in the project development. The functions of MyCloths includes user guide, search box, clothes categorizing, picture insertion using photo taken from camera or photo album, function for doing comparison between two clothes and function for suggestion of outfits.